Innovation platforms: synopsis of innovation platforms in agricultural research and development - Schut, Marc; Klerkx, Laurens; Kamanda, J.; Sartas, Murat; Leeuwis, Cees (Elsevier, 2019)
Innovation platforms are fast becoming part of the mantra of agricultural research and development projects and programs. Their basic tenet is that stakeholders depend on one another to achieve agricultural development outcomes, and hence need a space where they can learn, negotiate, and coordinate to overcome challenges and capitalize on opportunities through a facilitated innovation process. However, research and development funding and implementation agencies need to think critically about when, how, and in what form innovation platforms can contribute meaningfully to agricultural development outcomes. As the implementation of innovation platforms can consume significant human and financial resources, research and development donors will require evidence on their results and impact. This requires investments in structured Monitoring Evaluation and Learning, which is missing in many innovation platform initiatives. To reach target populations beyond the original scope of the platform and to enable scaling, innovation platforms should be firmly embedded in existing agricultural innovation and extension systems. Furthermore, the innovation platform approach must be complemented by other interventions that - together - aim at facilitating structural and wide-spread changes and impact towards sustainable food security.